THM (Thermo-hydro-mechanical) coupled mathematical model of fractured media and numerical simulation of a 3D enhanced geothermal system at 573 K and buried depth 6000–7000 M. (15th March 2015) - Zhao, Yangsheng; Feng, Zijun; Feng, Zengchao; Yang, Dong; Liang, Weiguo
Abstract: Hot dry rock geothermal energy is almost inexhaustible green energy. However, it makes slow progress in practice due to slow theory development. In this study, a three dimension thermo-hydro-mechanical coupled model of fractured media was established to simulate the extraction of HDR (Hot dry rock) geothermal energy based on the geological characteristics (geothermal gradient of 50 K/km, buried depth of 6250–6750 m) of Tengchong geothermal field in China. The simulation results show the variation in both field of temperature, stress, seepage and fracture aperture during heat extraction. The temperature in fracture face increased exponentially from injection well towards production well while extracting heat. The initial rock mass temperature of 573 K decreases to 423 K after 9-year running. The initial water pressure gradient in the fracture reached 0.17 MPa/m near the injection well and then decreased to 0.052 MPa/m after 1 year. The fracture aperture was triple of the initial value and the permeability coefficient increased by nine times over the 9-year operation period. That seepage resistance of artificial storage reservoir gradually decreased could improve extracting geothermal energy more efficiently. The amount of extracted heat declined exponentially with running time. The total extracted geothermal energy over 9 years was 5977 MWa and rock mass temperature decreased to 423 K. Highlights: A 3D thermo-hydro-mechanical coupled model of fractured media was established. Geothermal field featured by gradient of 50 K/km and 6250–6750 m was simulated. Fracture opening and pressure, stress, temperature change in deep HDR (Hot dry rock) development.